Quiet quitting, firing and hiring: just a social media trend? - Nunes,Ana Rita (2024)
Abstract The concept of Quiet Quitting (QQ) has recently gained prominence in social discussions. It is characterized by workers refusing to perform tasks beyond their contractual obligations. In the field of business management, some evidence has emerged linking QQ to two related phenomena: Quiet Firing (QF), where superiors restrict subordinates' career development opportunities, and Quiet Hiring (QH), a method for identifying employees who exceed their stated objectives. This study aim was to develop assessment instruments, drawing upon the limited existing literature, to facilitate the evaluation of QQ, QF, and QH constructs. This cross-sectional study includes a non-probabilistic sample of 118 professionally active Portuguese adults (M age = 38.9, SD = 11.5, 61.7% women) and was conducted online. An Exploratory Factor Analysis (EFA) was performed for all scales. The QQ scale comprises 13 items, the QH scale comprises 10 items, and EFA revealed a single factor for both, with reliability values within the recommended range (w QQ = .53; w QH = .50). The QF is composed of 13 items and 3 factors (Insatisfaction/Dropout, Professional Isolation, and Impediment to Professional Development). The proposed models should be tested in future studies to confirm their psychometric properties across different samples. The phenomena under examination may have impact on the well-being and work performance of employees.